The Liquidity and Liquidity Distribution Effects in Emerging Markets : The Case of Jordan - Vandenbussche, Jerome (IMF Working Papers; Working Paper, 2009)
This paper analyzes the determinants of daily changes in Jordan's interbank market overnight rate. It not only quantifies the classic liquidity effect, but also uncovers a liquidity distribution effect on both sides of the market, and shows that their magnitude is a decreasing and convex function of the level of excess reserves. It finds that the volatility of rate changes depends much more on the reserve surplus accumulated within a maintenance period than on the level of excess reserves. As Carpenter and Demiralp (2006), it uses the series of the central bank's daily forecast errors to identify the liquidity effect.